Closing the gender asset gap: Learning from value chain development in Africa and Asia - Quisumbing, Agnes R.; Rubin, Deborah; Manfre, Cristina; Waithanji, Elizabeth; van den Bold, Mara; Olney, Deanna K.; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2014)
This paper explores initial findings from four case studies in the Gender, Agriculture, and Assets Project on changes in gender relations in different agricultural interventions. It documents the adaptive measures projects are taking to encourage gender-equitable value chain projects. Findings suggest that the dairy and horticulture value chain cases have successfully increased the stock of both men’s and women’s tangible assets and those assets they own jointly.